Framing work and welfare: Insights from the growing relevance of company welfare in Italy. (April 2021) - Gasparri, Stefano
This article applies the concept of frames of reference to contemporary work and welfare dynamics by focusing on the growing relevance of company welfare in Italy after the 2008 crisis. The analysis considers how this occurred along three phases: in the first, a path-breaking case, Luxottica, demonstrates the potential of company welfare; then, Renzi's government promotes company welfare through tax breaks; finally, trade unions try to affect the diffusion of company welfare, displaying contrasting ideologies as well as pragmatic joint solutions in the process. Overall, two contiguous sub-frames – consultative unitarism and collaborative pluralism – offer the mainstream justification to the events and the policy debate around them, a debate in which the industrial relations scholarship played a key role. However, a critical interpretation is present too, suggesting that the relevance of company welfare is driven by the mobilisation of a political and economic elite and results in few cases of positive employment relations alongside broad social and economic imbalances.